Proceedings of the 2020 3rd International Conference on Big Data Technologies 2020
DOI: 10.1145/3422713.3422754
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model integrating UTAUT and ECM with espoused cultural values for investigating users' continuance intention of using mobile payment

Abstract: Mobile payment (M-payment), as an emerging financial transaction method has been widely adopted in various contexts. In order to investigate the significance factors and espoused cultural moderators impacting users' M-payment continuance usage intention in China, this study proposes a comprehensive model integrating Unified Theory of Acceptance and Use of Technology (UTAUT) and Expectancy Confirmation Model (ECM) with trust variable espoused by Hofstede's cultural value to investigate factors affecting users' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Five items for computer self-efficacy were adopted from John (2015) and Ebijuwa and Mabawonku (2019). Six items were adopted from Xie et al (2020) and Zhao and Bacao (2020) to measure confirmation. All adopted items were slightly customized to fit the context and aim of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Five items for computer self-efficacy were adopted from John (2015) and Ebijuwa and Mabawonku (2019). Six items were adopted from Xie et al (2020) and Zhao and Bacao (2020) to measure confirmation. All adopted items were slightly customized to fit the context and aim of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0265-671X.htm Previous research concentrated on M-payment adoption (Al-Sharafi et al, 2021) but there has been minimal focus on CI in mobile payments until recently when several studies were conducted (Singh, 2020;Zhao and Bacao, 2020;Loh et al, 2021). Correspondingly, this study addresses the highlighted research gap by examining customer behavior post-M-payment adoption, including the under-explored area of CI.…”
Section: Mobile Payment Service Quality 2019mentioning
confidence: 99%
“…An empirical study concluded the integrated model can better predict CI for M-pay, and key factors are trust, satisfaction and performance and effort expectancies (Singh, 2020). Another study presented a detailed model incorporating UTAUT and ECM with a trust variable to examine elements impacting CI for M-payment (Zhao and Bacao, 2020). Whilst most existing research concentrated on how satisfaction impacts CI for M-payment (Hussain et al, 2019;Singh, 2020), SQ is also significant (Jin and Lim, 2021).…”
Section: Mobile Payment Service Quality 2019mentioning
confidence: 99%
“…Individualism is typical of societies in which people's ties among themselves are weak, whereas collectivism is present in societies in which people are integrated from birth into strong, cohesive groups. Users in individualistic cultures are more likely to adopt new purchasing technologies (Zhang et al, 2018;Chopdar & Sivakumar, 2019;Zhao & Bacao, 2020), are less affected by the opinion of their peers, and are more focused on efficiency, speed, and performance (Alcántara-Pilar et al, 2017;Srite & Karahanna, 2006). Lim et al (2004) propose that, by contrast, users in countries with greater collectivism have a lower intention to adopt new purchasing technologies through online platforms.…”
Section: The Moderating Effect Of National Culture On Intention To Usementioning
confidence: 99%